SNP in starch biosynthesis genes associated with nutritional and functional properties of rice - Kharabian-Masouleh, Ardashir; Waters, Daniel L. E.; Reinke, Russell F.; Ward, Rachelle; Henry, Robert J. (Springer, 2012)
Starch is a major component of human diets. The relative contribution of variation in the genes of starch biosynthesis to the nutritional and functional properties of the rice was evaluated in a rice breeding population. Sequencing 18 genes involved in starch synthesis in a population of 233 rice breeding lines discovered 66 functional SNPs in exonic regions. Five genes, AGPS2b, Isoamylase1, SPHOL, SSIIb and SSIVb showed no polymorphism. Association analysis found 31 of the SNP were associated with differences in pasting and cooking quality properties of the rice lines. Two genes appear to be the major loci controlling traits under human selection in rice, GBSSI (waxy gene) and SSIIa. GBSSI influenced amylose content and retrogradation. Other genes contributing to retrogradation were GPT1, SSI, BEI and SSIIIa. SSIIa explained much of the variation in cooking characteristics. Other genes had relatively small effects.